The Mexico-Canada border: extraterritorial border control and the production of 'economic refugees'. (2018) - Young, Julie E.E.
By examining the Mexico-Canada border, I argue that the interplay between discourses of the 'bogus economic refugee' and Canada's extraterritorial bordering practices is crucial to understanding human security in North America. The concept of the Mexico-Canada border is shorthand for how Canadian policies and practices aim to police Mexico's borders. For example, Canada implemented a visa requirement in 2009 in response to a 'surge' in refugee claims by Mexican nationals. The term also signals how Mexico has been constructed as the focus of regional migration management, including through Canada's Anti-Crime Capacity Building Program to support policing and border security efforts within Mexico. Both initiatives contribute to a broader Canadian strategy of Mexican refugee deterrence.